The crustal evolution of South America from a zircon Hf‐isotope perspective. (16th February 2016) - Augustsson, Carita; Willner, Arne P.; Rüsing, Tobias; Niemeyer, Hans; Gerdes, Axel; Adams, Christopher J.; Miller, Hubert
Abstract: Hf‐isotope data of >1100 detrital zircon grains from the Palaeozoic, south‐central Andean Gondwana margin record the complete crustal evolution of South America, which was the predominant source. The oldest grains, with crustal residence ages of 3.8–4.0 Ga, are consistent with complete recycling of existing continental crust around 4 Ga. We confirm three major Archaean, Palaeoproterozoic (Transamazonian) and late Mesoproterozoic to early Neoproterozoic crust‐addition phases as well as six igneous phases during Proterozoic to Palaeozoic time involving mixing of juvenile and crustally reworked material. A late Mesoproterozoic to early Neoproterozoic, Grenville‐age igneous belt can be postulated along the palaeo‐margin of South America. This belt was the basement for later magmatic arcs and accreted allochthonous microcontinents as recorded by similar crustal residence ages. Crustal reworking likely dominated over juvenile addition during the Palaeozoic era, and Proterozoic and Archaean zircon was mainly crustally reworked from the eroding, thickened Ordovician Famatinian arc.